The Mediating Role of Job Satisfaction in the Relationship between Work-Life Balance, Continuance Commitment, Task Complexity, and Competence on Perceived Productivity - Zumrodah, Zumrodah; Negoro, Dhimas Angga (Malikussaleh University, Aceh, Indonesia, 2025)
This study examines the mediating role of job satisfaction in the relationship between work-life balance, continuous commitment, task complexity, and competencies on employees' perceived productivity at the Ministry of Tourism and Creative Economy. This study used the Structural Equation Modelling–Partial Least Squares (SEM–PLS) approach to analyze data from 231 participants. Important components of an effective workplace, such as job satisfaction and perceived productivity, are strongly impacted by work-life balance and continual dedication, according to the results. In contrast, task complexity hurts both job satisfaction and perceived productivity. Meanwhile, competencies positively influence perceived productivity but do not directly affect job satisfaction. In addition, competency-based relationships are not mediated by job satisfaction, although work-life balance, sustained commitment, and task complexity are all related to perceived productivity. Human resource management, which promotes a healthy work-life balance, increases dedication over time, and controls the complexity of jobs, is crucial, according to the study's conclusions. Policies such as flexible working hours, structured training, and clear task distribution can enhance job satisfaction and perceived productivity. These findings are relevant for optimizing the performance of the tourism and creative economy sectors, supporting industry growth, and increasing their contribution to the national economy.